HIV Patients in the HCUP Database: A Study of Hospital Utilization and Costs - Fred J. Hellinger (SAGE Publishing, 2004)
This study examines the utilization of hospital care by HIV patients in all hospitals in eight states (California, Colorado, Florida, Kansas, New Jersey, New York, Pennsylvania, and South Carolina), and examines the cost of hospital care for HIV patients in six of these states (California, Colorado, Kansas, New Jersey, New York, and South Carolina). The eight states in the sample account for more than 52% of all persons living with AIDS in the United States; the six states account for 39%. The unit of observation in both studies is a hospital admission by a patient with HIV. Hospital data were obtained from the Healthcare Cost and Utilization Project (HCUP), State Inpatient Database (SID), which is maintained by the Agency for Healthcare Research and Quality (AHRQ). The HCUP contains hospital discharge data and is a federal/state/industry partnership to build a multistate health care data system. Using multivariate analytic techniques and data from 2000, results indicate that cost and length of a hospital stay vary significantly across states after accounting for a patient's gender, insurance type, race, age, and number of diagnoses, as well as the teaching status and ownership category of the hospital.